2017
DOI: 10.1016/j.semcdb.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Atoh1 in sensory hair cell development: constraints and cofactors

Abstract: The proneural gene, Atoh1, is necessary and in some contexts sufficient for early inner ear hair cell development. Its function is the subject of intensive research, not least because of the possibility that it could be used in therapeutic strategies to reverse hair cell loss in deafness. However, it is clear that Atoh1's function is highly context dependent. During inner ear development, Atoh1 is only able to promote hair cell differentiation at specific developmental stages. Outside the ear, Atoh1 is require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 112 publications
(109 reference statements)
1
16
0
Order By: Relevance
“…Transcription factors regulate the temporal and spatial patterns of gene expression within the cells of complex tissues, establishing cell fate, and ultimately determining their morphological and functional properties ( Lemon and Tjian, 2000 ; Levine and Tjian, 2003 ; Zhang et al, 2004 ). Within the inner ear, expression of Atoh1 , a bHLH class transcription factor ( Lo et al, 1991 ; Ross et al, 2003 ) is both necessary and sufficient for the induction of sensory hair cells in the embryonic and neonatal cochlea, and ultimately plays an integral role in initiating the hair cell gene expression program ( Bermingham et al, 1999 ; Zheng and Gao, 2000 ; Woods et al, 2004 ; Kelly et al, 2012 ; Chonko et al, 2013 ; Cai et al, 2013 ; Ryan et al, 2015 ; Scheffer et al, 2015 ; Stojanova et al, 2016 ; Costa et al, 2017 ). However, previous studies have shown that Atoh1 expression alone is not sufficient to induce hair cell differentiation in somatic cells ( Izumikawa et al, 2008 ; Costa et al, 2015 ; Abdolazimi et al, 2016 ), or mature supporting cells of the organ of Corti ( Kelly et al, 2012 ; Liu et al, 2012b ).…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factors regulate the temporal and spatial patterns of gene expression within the cells of complex tissues, establishing cell fate, and ultimately determining their morphological and functional properties ( Lemon and Tjian, 2000 ; Levine and Tjian, 2003 ; Zhang et al, 2004 ). Within the inner ear, expression of Atoh1 , a bHLH class transcription factor ( Lo et al, 1991 ; Ross et al, 2003 ) is both necessary and sufficient for the induction of sensory hair cells in the embryonic and neonatal cochlea, and ultimately plays an integral role in initiating the hair cell gene expression program ( Bermingham et al, 1999 ; Zheng and Gao, 2000 ; Woods et al, 2004 ; Kelly et al, 2012 ; Chonko et al, 2013 ; Cai et al, 2013 ; Ryan et al, 2015 ; Scheffer et al, 2015 ; Stojanova et al, 2016 ; Costa et al, 2017 ). However, previous studies have shown that Atoh1 expression alone is not sufficient to induce hair cell differentiation in somatic cells ( Izumikawa et al, 2008 ; Costa et al, 2015 ; Abdolazimi et al, 2016 ), or mature supporting cells of the organ of Corti ( Kelly et al, 2012 ; Liu et al, 2012b ).…”
Section: Introductionmentioning
confidence: 99%
“…The capacity for regeneration decreases in the adult and multiple mechanisms might account for this, including epigenetic silencing of key regulators and their targets or downregulation of the activity of key signaling pathways, such as Notch and Wnt, and transcription factors, such as Atoh1, involved in hair cell formation. Atoh1 expression decreases during organ maturation, and cells in the cochlear sensory epithelium respond to Atoh1 induction by differentiating into hair cells only within a limited time window (Basch et al, 2016a,b;Costa et al, 2017;Kelly et al, 2012). This drop in regenerative potential could be due to epigenetic changes at the Atoh1 locus (Stojanova et al, 2016), reduced chromatin accessibility of Atoh1 transcriptional targets (Jen et al, 2019;Stojanova et al, 2016) or the lack of factors that might cooperate with Atoh1 to promote hair cell differentiation, such as Gfi1 and Pou4f3 (also known as Brn3c) (Costa et al, 2017) or Isl1 (Yamashita et al, 2018).…”
Section: Mammalian Regenerationmentioning
confidence: 99%
“…and 2). Wnt signaling induces the formation of hair cells by upregulating the expression of ATOH1, whereas Notch signaling triggers the formation of supporting cells by downregulating the expression of ATOH1 (Pan et al, ; Shi et al, ; Costa et al, ; Li et al, ). These biological events are also essential for mitotic and non鈥恗itotic regeneration of hair cells that is governed by the Wnt and Notch signaling pathways in the non鈥恗ammalian vertebrates (Jiang et al, ).…”
Section: Notch and Wnt Signalingmentioning
confidence: 99%